2000
DOI: 10.1074/jbc.m004451200
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori-selective Antibacterials Based on Inhibition of Pyrimidine Biosynthesis

Abstract: We report the discovery of a class of pyrazole-based compounds that are potent inhibitors of the dihydroorotate dehydrogenase of Helicobacter pylori but that do not inhibit the cognate enzymes from Gram-positive bacteria or humans. In culture these compounds inhibit the growth of H. pylori selectively, showing no effect on other Gram-negative or Gram-positive bacteria or human cell lines. These compounds represent the first examples of H. pylori-specific antibacterial agents. Cellular activity within this stru… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
53
0

Year Published

2001
2001
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(55 citation statements)
references
References 23 publications
(27 reference statements)
2
53
0
Order By: Relevance
“…H. pylori has no homologs of the pyrimidine salvage enzymes uracil PRTase (Upp) or uridine kinase (Udk), which convert uracil to UMP (37). Although our results could be explained by poor uptake of medium supplements, they are consistent with recent reports that the conserved gene HP1084 (pyrB), encoding aspartate carbamoyltransferase, is also essential (13) and that inhibitors of dihydroorotate dehydrogenase (PyrD) are lethal to H. pylori (17). Taken together these data appear to demonstrate that de novo pyrimidine biosynthesis is required for survival of H. pylori.…”
Section: Resultssupporting
confidence: 82%
See 1 more Smart Citation
“…H. pylori has no homologs of the pyrimidine salvage enzymes uracil PRTase (Upp) or uridine kinase (Udk), which convert uracil to UMP (37). Although our results could be explained by poor uptake of medium supplements, they are consistent with recent reports that the conserved gene HP1084 (pyrB), encoding aspartate carbamoyltransferase, is also essential (13) and that inhibitors of dihydroorotate dehydrogenase (PyrD) are lethal to H. pylori (17). Taken together these data appear to demonstrate that de novo pyrimidine biosynthesis is required for survival of H. pylori.…”
Section: Resultssupporting
confidence: 82%
“…Importantly, a further degree of selectivity may be conferred by the fact that the nearest neighbors of some of these genes are not required for viability in other bacteria. The potential of this type of approach has been graphically illustrated by the recent identification of pyrazole-based anti-H. pylori compounds which specifically inhibit the pyrimidine biosynthesis enzyme PyrD in H. pylori but are inactive against orthologous enzymes in other bacteria and humans (17). We therefore suggest that the products of these highly diverged essential genes merit further investigation as potential targets for novel, highly specific anti-H. pylori agents.…”
Section: Resultsmentioning
confidence: 99%
“…The R265A mutation affected some compounds by up to 35-fold, whereas there was no effect on others. This site is also thought to bind CoQ, although direct structural evidence for the CoQ site is still lacking (12,14,31). In support of a common binding site for the malaria enzyme, the most potent benzamidine derivatives (compound 6) appeared to be a simple competitive inhibitor with respect to CoQ utilization.…”
Section: Discussionmentioning
confidence: 99%
“…1). Thirdly, species-selective pyrazole-based inhibitors of Hylicobacter pylori and of Escherichia coli DHODH have been reported that were identified by highthroughput screening of chemical libraries (13,14). Finally, we previously demonstrated that P. falciparum DHODH is poorly inhibited by the potent human DHODH inhibitors redoxal, dichloroallyl lawsone, and A77-1726 analogs (15).…”
mentioning
confidence: 99%
“…An inhibitor of human DHODH (hDHODH) (A77 1726 the active metabolite of leflunomide) is marketed for the treatment of rheumatoid arthritis, illustrating that DHODH is a druggable target (10,11). Finally, biochemical (12,13) and structural studies (14,15) suggested that the identification of species-selective inhibitors against this target was feasible.…”
mentioning
confidence: 99%